Plastic shrinkage and cracking risk of recycled aggregates concrete. (15th September 2016) - Bendimerad, Ahmed Z.; Rozière, Emmanuel; Loukili, Ahmed
Highlights: The influence of recycled concrete on shrinkage induced cracking was investigated. Plastic shrinkage and other properties are correlated at early age. A model for Young modulus versus hydration degree was proposed. An approach based on tensile strength was used to assess the cracking sensitivity. The cracking sensitivity is not proportional to the recycled aggregate content. Abstract: This paper presents the results of experimental research on recycled concrete at early age. The influence of recycled gravel and sand (RG and RS) and initial water saturation of RG on plastic shrinkage and cracking sensitivity was investigated. Four initial water saturations were studied: 30%, 70%, 100% and 120% of saturated surface dried (SSD). The total water was kept constant for all the mixtures, so the added water was adjusted to take into account the absorption of the aggregates during the mixing process. Other concrete mixtures were designed using 30% and 100% of recycled gravel, and 30% of recycled sand. The gravel/sand ratios were adjusted to keep the maximum paste thickness (MPT) constant. To understand the evolution of early age parameters, a timeline was established and the analyses showed correlations between the evolution of plastic shrinkage and other properties at early age. The initial water saturation did not significantly affect the evolution of plastic shrinkage. Recycled aggregates actually show a relatively high rate of absorption during the first hour after mixing, i.e. before the development of plastic shrinkage. A stress/strength approach based on experimentally assessed parameters was used to compare the cracking sensitivity of different concretes with recycled aggregates. A high rate of substitution of recycled gravel or sand affected the early age properties of the recycled concrete and the cracking sensitivity especially when natural sand was replaced by recycled concrete sand.